2006
DOI: 10.1007/11663430_20
|View full text |Cite
|
Sign up to set email alerts
|

Towards Model Driven Engineering of Plastic User Interfaces

Abstract: Abstract. Ubiquitous computing has introduced the need for interactive systems to run on multiple platforms in different physical environments. Providing a user interface specially crafted for each context of use () is costly, may result in inconsistent behaviors [5] and above all is limited to the contexts of use that have been envisioned at design time. Opportunistic interaction in a changing environment requires enabling approaches and techniques for gracefully adapting the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 12 publications
(16 reference statements)
0
20
0
Order By: Relevance
“…The work of [19] is considered as one of the pioneering studies to join Model Driven Engineering with the domain of Human Computer Interaction. The reported approach has shown that the concepts of the MDE could be successfully applied to the UI engineering.…”
Section: Fig 1: the Four Main Stages Of Cameleon Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The work of [19] is considered as one of the pioneering studies to join Model Driven Engineering with the domain of Human Computer Interaction. The reported approach has shown that the concepts of the MDE could be successfully applied to the UI engineering.…”
Section: Fig 1: the Four Main Stages Of Cameleon Frameworkmentioning
confidence: 99%
“…The reported approach has shown that the concepts of the MDE could be successfully applied to the UI engineering. Sottet [19] proposes metamodels and models transformations to generate adaptable or plastic UI, and defines a general context meta-model. Based on the same approach (MDE), Hachani [20] suggest the introduction of the context of use at the tasks level rather than at the interactors level.…”
Section: Fig 1: the Four Main Stages Of Cameleon Frameworkmentioning
confidence: 99%
“…But practically only the variant platform is considered during the UI generation. Sottet [19] [20] is considered as one of the pioneers to have joined his work to the Model Driven Engineering and the domain of Human Computer Interaction (HCI). His approach makes it possible to show that the concepts of the MDE could be successfully applied to the UI engineering.…”
Section: State Of the Artmentioning
confidence: 99%
“…His approach makes it possible to show that the concepts of the MDE could be successfully applied to the UI engineering. Sottet [19] proposes meta-models and models transformations to generate adaptable UI, and defines a general context meta-model. Based on the same approach (MDE), Hachani [11] suggests the introduction of the context of use at the tasks level rather than at the interactors level.…”
Section: State Of the Artmentioning
confidence: 99%
“…It covers three information spaces: the user model, the platform model, and the physical and social environment model. UI adaptation has been addressed using many approaches over the years, including Machine Learning [21], Model-Driven Engineering (MDE) [8,17,18,32,33], and Component-oriented services [30]. Regardless of the approach, the tendency has been to focus on the functional aspects of adaptation.…”
Section: Introductionmentioning
confidence: 99%